Application of sulfur ylides in 1,2-difunctionalization of arynes via insertion into a C-S sigma-bond - Ahire, Milind M.; Thoke, Mahesh B.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel reactivity of sulfur ylides has been demonstrated in a transition-metal-free protocol to access ortho-substituted thioanisole derivatives by insertion of arynes into a C-S sigma-bond in moderate to good yields. The reaction involves the formation of C-C and C-S bonds and consecutive breaking of two C-S bonds under operationally mild reaction conditions.

Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant - Viswanadh, N. (Chemical Communications, 2018)
The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc)2 mediated regioselective, direct C–H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.